New types of marine risers for offshore engineering application - Toh, Fu Cai. (2013)
Marine offshore is a fast growing industry, majoring operations in drilling and production of oil reserves. Due to its strong demand in petroleum products around the world, drilling operations have moved from shallow to deep waters to cater for its needs. Hence the dependency of marine risers has grown. Marine risers are attached to the floating vessels or platforms as means of transportation for hydrocarbons products. Despite of the functionality of the marine risers, it is prone to fatigue stresses due to the long term effects of environmental conditions that would pose a threat to the sustainability of the risers. Therefore in this report, the aim is to portray the differences of the conventional risers such as hybrid, lazy wave and steep s configurations, determining the areas of their strengths and weaknesses. In turn, a new riser will be proposed to improve its performance in deep water conditions. Orcaflex is used to run the simulation of these configurations under regular and irregular waves. It was found that the hybrid riser produces the best performance in effective tension at hang off point and low bending moment at the bend interfaces. However, due to its complexity in fabrication and lack of field experience, the new riser is preferred as it produces effective tension and bending moment close to the values of hybrid configuration. This study may be useful for research students who are interested in the design and analysis of new riser in deep sea conditions.